Development of Interactive Learning Media Based on Articulate Storyline 3 For Arabic Language Learning in Senior High School (MAN Lumajang) - Nafisah, Ainun; Indrianto, Nino; Maulana, Asep (Abjadia : International Journal of Education, 2025)
This study aims to develop an interactive learning media application based on Articulate Storyline 3 in Arabic language learning as a solution to the low motivation and involvement of students due to the learning media used is still predominantly conventional in MAN Lumajang. The type of research used by researchers is research and development (RD). The development research is a research method that aims to produce a certain product. The research and development method is a scientific method used to research, design, create and test the validity of a product that has been created. In this development research, researchers used the four D model development model (4-D Model). The results of this study are validation from material experts showing a validity level of 85.2% and from media experts 89.6%, both of which are included in the very valid and very feasible category, although they require some revisions. Thus, this media is feasible to be used as an innovative alternative in the Arabic language learning process and is expected to increase student motivation and learning outcomes through a more interesting and interactive learning experience and so that it can be continued with a test of the effectiveness of the media on students.